2019
DOI: 10.1016/j.trci.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The cross‐sectional association of cognitive stimulation factors and cognitive function among Latino adults in Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: IntroductionHigher cognitive stimulation (CS) is associated with improved cognition. Sources of CS among Hispanics/Latinos are understudied.MethodsIn the Hispanic Community Health Study/Study of Latinos 2008 to 2011 (n = 9438), we used finite mixture models to generate latent CS profiles, and multivariate linear regressions to examine associations with cognition in Hispanic/Latino adults (45–74 years). CS included education, occupation, social network, and acculturation. Cognitive measures included the Six-Ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, the underlying mechanisms that may be driving these cognitive profiles were not directly examined. Work within HCHS/SOL and elsewhere suggests that other acculturation‐related variables beyond language preference 23 , 24 and additional social determinants of health that are known to influence cognitive performance generally, 25 may also be influencing the observed cognitive profiles. Moreover, there was an average difference of 7 years between baseline and SOL‐INCA visits, and we acknowledge that demographic, sociocultural, and health‐related covariates may have changed during that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the underlying mechanisms that may be driving these cognitive profiles were not directly examined. Work within HCHS/SOL and elsewhere suggests that other acculturation‐related variables beyond language preference 23 , 24 and additional social determinants of health that are known to influence cognitive performance generally, 25 may also be influencing the observed cognitive profiles. Moreover, there was an average difference of 7 years between baseline and SOL‐INCA visits, and we acknowledge that demographic, sociocultural, and health‐related covariates may have changed during that time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the underlying mechanisms that may be driving these cognitive profiles were not directly examined. Work within HCHS/SOL and elsewhere suggests that other acculturation-related variables beyond language preference 23,24 and additional social determinants of health that are known to influence cognitive performance generally, 25…”
Section: 34mentioning
confidence: 99%
“…The scores of each question range from 1 ( three or more times a week ) to 6 ( less than once a year or never ) and then the coding was reversed. An average score of three questions was later calculated with a range between 1 and 6 (Vásquez et al, 2019). The mean scores of contact frequency of two dimensions were used.…”
Section: Family Relationshipmentioning
confidence: 99%
“…Structural support of family seems to be important to older Hispanics since they have a higher tendency to reside with more kids and adults in comparison with other ethnic/racial groups (Olsen et al, 2019) and have large family networks (Gallo et al, 2009). Research has indicated more family connections acting as higher cognitive stimulation were positively associated with cognitive function for Hispanics (Katz et al, 2020; Vásquez et al, 2019). In addition, the contact frequency with network members which is not included in the social support theory is also considered as one aspect of network structure by many researchers (Berkman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%